2012
DOI: 10.4236/oje.2012.21005
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and water-use conflicts in Lake Taabo (Ivory Coast)

Abstract: The Lake Taabo (Ivory Coast, Africa) results of the construction of the Taabo dam on the Bandama River. The changes in the water level of the 69-km² lake depend on 1) the rainfall linked to alternating dry/wet seasons; 2) the extraction of water for human uses; 3) the discharge of water from the upstream dam and the volumes tur-bined by the Kossou dam; 4) the various anthropic effects (discharge of untreated waste water from towns and industries, and leaching from agricultural land). The average concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The Kossou reservoir covers an area of 1700 km 2 in the center part of the country. The Taabo reservoir, located 120 km downstream of the Kossou reservoir, covers an area of 62 km 2 [6,16]. The Fae hydroelectric dam covers an area of 16.28 km 2 located in South-western region of Ivory Coast [17].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The Kossou reservoir covers an area of 1700 km 2 in the center part of the country. The Taabo reservoir, located 120 km downstream of the Kossou reservoir, covers an area of 62 km 2 [6,16]. The Fae hydroelectric dam covers an area of 16.28 km 2 located in South-western region of Ivory Coast [17].…”
Section: Study Areamentioning
confidence: 99%
“…Watershed of Taabo, Kossou and Fae hydroelectrics reservoirs covers, an area of 58700 km 2 , 32400 km 2 and 2424 km 2 respectively. These watersheds are mostly composed by rural area and agriculture [6,7]. Invasive aquatic plants are present and occupy a large part of the surface of the different water bodies.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The high rate of urbanisation, combined with agriculture expansion, are susceptible to impact aquatic ecosystems, especially those of the freshwaters, in this country. Pollution of aquatic ecosystems from the discharge of untreated domestic, industrial, and agricultural wastes have been reported in the country [17][18][19]. Regarding the climate of this country, from the 1980s to 2000s temperature increased on average by 0.5 °C, and from 2001 to 2010 a temperature rise of 0.8 °C was recorded [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although some data are available on physical, chemical and phytoplanktonic characteristics of Lake Taabo (Groga et al, 2012), there are no data on phytoplankton biomass and functional groups of this lake. Thus, this research focused on determining the ecological quality of the lake's waters by analysing the structure of phytoplankton functional groups in relation to the environmental parameters.…”
Section: Introductionmentioning
confidence: 99%